IDENTIFIKASI GUNUNG API PURBA DI DAERAH SAPAYA, SULAWESI SELATAN PADA DATA INDERAAN JAUH - Sidarto Sidarto; Udi Hartono (Pusat Survei Geologi, 2009)
In Tertiary, the South Arm of Sulawesi Island is a volcanic arc represented by Camba Formation having a relatively wide distribution. Integration of landsat and IFSAR images is able to visualize volcanic morphological features, lithology and volcanic structures that are used to identify ancient volcanoes in Sapaya area and surroundings. The result of geological interpretation on the images indicated there were two ancient volcanoes in this area, involving Sapaya and Bantoloe Volcanoes. The Middle Miocene - Pliocene Sapaya Volcano shows eroded cone feature, consisting of breccia volcanic (proximal facies), tuff (medial facies), and conglomerate (distal facies) units, and the vokanic structures are caldera, and radier intrusion basalts; while the Pliocene Bantoloe Volcano is identified by an eroded cone morphology, consisting of volcanic breccia of Bentoloe (proximal facies), lava Bantoloe (central testes), and diorite showing a deep seated intrusion (central facies). The Sapaya Volcano might be controlled by Tithyan type subduction showing a collision between micro continental which is part of Australian Continent and Eurasian Continent Plates. Keywords: South Arm Sulawesi, morphology, lithology, volcanic structure, ancient volcanoes, landsat and IFSAR Images